Selective Alcohol Electrooxidation by ZIF-8 Functionalized Pt/Carbon Catalyst - Essbach, Claudia; Senkovska, Irena; Unmuessig, Tobias; Fischer, Anna; Kaskel, Stefan (ACS Applied Materials and Interfaces, 2019)
Highly selective electrooxidation catalysts were synthesized by functionalizing a commercially available reference electrooxidation catalyst (Pt/Vulcan XC 72R) with a coating of the highly hydrophobic porous zeolitic imidazolate framework ZIF-8, an adsorbent with high affinity for the extraction of aliphatic alcohols from water. According to cyclovoltammetric studies in alkaline media at 25 °C, the ZIF-8 functionalized catalyst shows a high selectivity for the electrooxidation of small alcohols such as ethanol and methanol over more hydrophobic alcohols (n-butanol, n-propanol). In contrast, the noncoated reference catalyst (Pt/Vulcan XC 72R) oxidizes all investigated alcohols with comparable current densities. Tafel curves confirm these observations and indicate a limited conversion of long chain alcohols, especially n-butanol, caused by the high affinity of the ZIF-8 for this molecule resulting in significant diffusion limitations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: elctrocatalysis; eletrocatalytic alcohol oxidation; MOF composite; MOF functionalized electrocatalyst; Pt/Vulcan XC 72R; ZIF-8